AB0287 Increased expression of CD95 in B cells of 2nd cycle rituximab non-responders. (23rd January 2014) - Brezinschek, H.-P.; Rainer, F.; Lunzer, R.; Graninger, W.B.
Abstract : Background: Recently, we have shown that in an Austrian rituximab-registry RA-patients with a low percentage of CD95 + post-switch B cells will benefit more profoundly from a B cell depleting therapy. Objectives: The purpose of this study was to test whether the frequency of CD95 positive cells within the different B cell subsets would be useful to identify non reponders to rituximab ahead of time. Methods: Patients with active rheumatoid arthritis despite therapy with TNF-inhibitors were included in the Austrian B Cell surveillance (ABS)-register. DAS28 was determined before and 24 weeks after each rituximab cycle. In addition, peripheral blood mononuclear cells were isolated before the first infusion of a rituximab therapy. Cells were stained with monoclonal antibodies directed towards CD19, CD24, CD27, CD38, CD45 and IgD. To exclude T cells and monocytes CD3 and CD14 were utilized. Five hundred thousand cells were acquired and analyzed using a seven-channel flow cytometry (BD Canto II cytometer, Software FACSDiva). According to their surface staining B cells were divided in naive (CD19+, IgD+, CD27-); IgD memory (CD19+, IgD+, CD27+), post switch (CD19+, IgD-, CD27+) and double negative (CD19+, IgD-, CD27-) cells. In addition, B cells were further characterized using CD95 and CD80. Results: Twenty six patients have undergone the week 24-analysis after a second cycle of rituximab. Ten patients had a good (38%), 6 a moderate (23%) and 10 (38%) had no EULAR-response. In the non-responder group the frequency of CD95 + naïve and pre-switch memory B cells was significantly higher compared to responders and healthy controls. Thus, the mean ± SE percent of naïve B cells before the second cycle in nonresponders was 52.8±11.6, 19.1±5.6 in responders (p≤0.0048) and 5.4±0.9 in controls (p≤0.0001), respectively. Within the pre-switch B cell population non-responders had 88.7% ± 14.3 CD95 positive B cells, compared to 72.2% ± 5.3 in responders (p≤0.04) and 38.8% ± 3.0 in controls (p≤0.0001). No significant difference were found between responders and nonresponders in the other B cell subpopulations. Conclusions: Our preliminary results suggest that the analysis of B cell subsets may help to discriminate 2nd cycle rituximab-responders from non-responders. The percentage of CD95 + naive B cells may be a candidate marker for the prediction of a therapeutic response to rituximab in RA. Disclosure of Interest: None Declared